2010
DOI: 10.1080/02640414.2010.507250
|View full text |Cite
|
Sign up to set email alerts
|

Motor variability in sports: A non-linear analysis of race walking

Abstract: This aim of this study was to analyse the nature of movement variability and to assess whether entropy measures may represent a valuable synthetic index of neuromuscular organization. The regularity of kinematic/kinetic time series during race walking, the changes in the structure of intra-individual variability over the test session, and the influence of athletic skill in (inter)national rank athletes were investigated. Motion analysis techniques were used. Sample entropy (SampEn) was adopted to examine fluct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 28 publications
2
59
4
Order By: Relevance
“…Whatever the case may be, the ApEn values from the original time series and surrogate data tests show differences in their rate of increase; however, the increased values are consistent with the results reported by precedent studies (Bartlett, Wheat, & Robins, 2007;Riley & Turvey, 2002). Based on these results, it is believed that in both young and elderly women groups, the periodicity of lower extremity joint flexion/extension motion possesses not only noise during walking but also a non-linear structure, indicating a functional information on the neuroskeletal system (Preatoni et al, 2010).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Whatever the case may be, the ApEn values from the original time series and surrogate data tests show differences in their rate of increase; however, the increased values are consistent with the results reported by precedent studies (Bartlett, Wheat, & Robins, 2007;Riley & Turvey, 2002). Based on these results, it is believed that in both young and elderly women groups, the periodicity of lower extremity joint flexion/extension motion possesses not only noise during walking but also a non-linear structure, indicating a functional information on the neuroskeletal system (Preatoni et al, 2010).…”
Section: Discussionsupporting
confidence: 81%
“…In the present study, both the young and elderly women groups showed a statistically significant increase in the ratios of surrogate ApEn values of the hip, knee, and ankle flexion/extension motion to those of the original data between the groups. Preatoni et al (2010) reported an increase of 59% in the SampEn value after a surrogate data test on hip flexion/extension angle data of race walking athletes, which was higher than the results in the present study. It is believed that such a difference may be attributed to movement speed and other factors.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…A further approach, based on sophisticated mathematical methods applied to race walking biomechanics, has been carried out in several investigations (Preatoni et al, 2010a;Preatoni, Ferrario, Donà, Hamill & Rodano, 2010b;Donà et al, 2009). Their outcomes may support researchers with functional guidelines and provide coaches with quantitative tools for skill prediction (Donà et al, 2009) and technique assessment (Preatoni et al, 2010b): i) a sequential estimation procedure defined that at least 15 trials are necessary for a reliable description of the kinematical parameters investigated, ii) a non-linear analysis based on entropy (measurement of the motor variability) may reflect the athletic condition and the performance enhancement due to a motor learning/adaptation, iii) a multivariate data analysis (functional Principal Component Analysis, fPCA) found differences in knee joint kinematics across athletes level.…”
Section: Kinematicsmentioning
confidence: 99%